O princípio da anualidade e as modificações na interpretação do direito eleitoral pelo poder judiciário - Paulo Henrique de Mattos Studart (2016)
The 16th article of the Constitution of the Federative Republic of Brazil provides that the law that alters the electoral procedure shall not be applied to the election to be held within one year of the date of its edition. This principle, differing in time the application of the electoral law, reveals itself as an instrument geared to protect the normality and legitimacy of the electoral process and the exercise of political rights. However, it is a reality that the courts often changes their interpretation of the law without any formal change in the legal texts. In this context, the abrupt change in the interpretation of the law by the Electoral Courts, either by editing a resolution, responding to a query, or by judging a case, exerts enormous influence on the legal framework ruling the electoral process. This is the context from which the inquiry of this research is made: the scope of protection conferred by the 16th article of the Constitution of the Federative Republic of Brazil is restricted to the formal legislative process? Or also reaches the Judiciary, especially the Electoral Courts, when, in the exercise of its duties, promotes changes in the interpretation of the elections law? The present study investigates this question by analyzing in depth the 16th article of the Constitution of the Federative Republic of Brazil, its relation to legal certainty and equal opportunities in elections, through understanding how the electoral process provides legitimacy to the political representation and the exercise of the political rights by the citizens.